Surgical Management of Calcific Metamorphosis of Pulp: A Case Report - Kulsum, U; Farzana, F (BIRDEM Medical Journal, 2012)
A case is reported which states calcific metamorphosis of pulp in a mandibular left lateral incisor and concomitant pulp necrosis of both central incisors for a single trauma. There was a large periapical lesion associated with the teeth. Conventional endodontic treatment was performed on teeth with pulp necrosis, but the canal with calcific metamorphosis could not be negotiated with endodontic files. The periapical lesion was surgically removed and diagnosed as acute periapical abscess on histopathology. During the surgical procedure root apices of calcified tooth as well as other teeth were removed and retrograde cavity was prepared and filled with glass ionomer cement i.e apicectomy was done. The bony defect was filled with calcium hydroxyappatite crystal. Six months later the teeth were asymptomatic and radiological follow-up showed gradual healing of the bony cavity. DOI: http://dx.doi.org/10.3329/birdem.v1i1.12396 Birdem Med J 2011; 1(1): 46-50